INNOVATIVE TECHNOLOGIES ARE THE DRIVING FORCE OF EDUCATIONAL DEVELOPMENT - Mokhinur Khazratullo qizi Sotvoldieva (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
Today, helping young people to find a worthy place in society is one of the important and priority tasks facing developing countries today. At the core of them, the field of education occupies the main place. In this research, we will discuss the future of the state directly depends on educated youth and their quality education, the stages of development of education in our country.